Reduced Circulating Endothelial Progenitor Cells and Downregulated GTCPH I Pathway Related to Endothelial Dysfunction in Premenopausal Women with Isolated Impaired Glucose Tolerance - Juan Liu; Xiangbin Xing; Xinlin Wu; Xiang Li; Shun Yao; Zi Ren; Haitao Zeng; Shaohong Wu (Cardiology Research and Practice)
Background. Individuals at a prediabetic stage have had an augmented cardiovascular disease (CVD) risk and CVD-related mortality compared to normal glucose tolerance (NGT) individuals, which may be attributed to the impaired vascular endothelial repair capacity. In this study, circulating endothelial progenitor cells’ (EPCs) number and activity were evaluated, and the underlying mechanisms in premenopausal women with impaired glucose regulation were explored. Methods. Circulating EPCs’ number and activity and flow-mediated dilation (FMD) were compared in premenopausal women with NGT, isolated impaired fasting glucose (i-IFG), or isolated impaired glucose tolerance (i-IGT). Plasma nitric oxide (NO), EPCs-secreted NO, and intracellular BH4 levels were also measured. The key proteins (Tie2, Akt, eNOS, and GTPCH I) in the guanosine triphosphate cyclohydrolase/tetrahydrobiopterin (GTPCH/BH4) pathway and Tie2/Akt/eNOS signaling pathway were evaluated in these women. Results. It was observed that the i-IGT premenopausal women not i-IFG premenopausal women had a significant reduction in circulating EPCs’ number and activity as well as reduced FMD when compared to NGT subjects. Plasma NO levels or EPCs-secreted NO also decreased only in i-IGT women. The expression of GTCPH I as well as intracellular BH4 levels declined in i-IGT women; however, the alternations of key proteins’ expression in the Tie2/Akt/eNOS signaling pathway were not observed in either i-IGT or i-IFG women. Conclusions. The endothelial repair capacity was impaired in i-IGT premenopausal women but was preserved in i-IFG counterparts. The underlying mechanism may be associated with the downregulated GTCPH I pathway and reduced NO productions.